News from the BIPM laboratories—2020. (21st January 2021) - Wielgosz, Robert; Tavella, Patrizia; Judge, Steven; Stock, Michael; Milton, Martin
Abstract: In order to fulfil its mission to ensure and promote the global comparability of measurements, the BIPM operates laboratories in the fields of physical metrology, time, ionizing radiation and chemistry. These laboratories act as centres for scientific and technical collaboration between member states providing capabilities for international measurement comparisons on a shared cost basis. They coordinate international comparisons of national measurement standards agreed to be of the highest priority, and they establish and maintain appropriate reference standards for use as the basis of key international comparisons at the highest level and provide selected calibrations from them. The BIPM sustained all of its key activities throughout the periods of confinement resulting from the global pandemic in 2020 including: the publication of Circular T each month, the annual World Metrology Day celebrations and the launch of the new key comparison database (KCDB 2.0). Several activities were brought forward in the work programme including the automation of data handling in the International Reference System (SIR) for radionuclide metrology and on-line technical exchanges and capacity building initiatives. The BIPM has also worked to understand how best to support the National Metrology Institutes (NMIs) as a 'new normal' emerges. As a first step, the NMI 'COVID action' repository was implemented and two pilot studies were launched by the CCQM on the measurement of SARS-CoV-2 and SARS-CoV-2 antibodies. New ways have been developed to support the International Committee for Weights and Measures (CIPM) consultative committees on-line. For example, during 2020 a total of 70 video meetings were held for the CCQM, with similar trends for other CCs. In the following sections, we provide highlights of the work the laboratories have undertaken during 2020.